Systemic effects of inhaled corticosteroids. Various pending questions. - Ferreira, M B (1997)
Inhaled steroids play a central and undisputed role in the management of Bronchial Asthma, since inflammation has been recognised as the main physiopathological mechanism in this disease. Indeed, the earlier introduction of inhaled steroids in the therapy of Bronchial Asthma is currently being recommended by several authors. However, accompanying the much broader use of these drugs, concerns about the possibility of induction of adverse systemic effects have appeared more and more frequently in the medical community and in medical literature. This article addresses the main concerns related to the systemic effects of inhaled corticotherapy, critically reviewing the clinical significance of some of the more relevant published studies.